Study of Optical Fiber Design Parameters in Fiber Optics Communications - Mohammed, Salim Qadir; Asaad M. Al-Hindawi, Asaad M. (Kurdistan Journal of Applied Research, 2017)
Fiber optics is an important part in the telecommunication infrastructure. Large bandwidth and low attenuation are features for the fiber optics to provide gigabit transmission. Nowadays, fiber optics are used widely in long distance communication and networking to provide the required information traffic for multimedia applications. In this paper, the optical fiber structure and the operation mechanism for multimode and single modes are analyzed. The design parameters such as core radius, numerical aperture, attenuation, dispersion and information capacity for step index and graded index fibers are studied, calculated and compared for different light sources.